Gender, Race, Class, and the Politics of Schooling in the Inner City. Issue 1 (September 2017) - Gadsden, Vivian L.
The politics of gender, race, and class are present within and outside of schools, and are pivotal issues raised in the policies and practices of schooling. This article focuses on the ways in which gender, race, and class are addressed within institutional practices and politics, both historically and in contemporary inner-city schooling. I examine gender, race, and class as integrated or intersectional identities, rather than as isolated status categories. The discussion highlights experiences and perspectives of African American youth who identify as girls to depict the complex intersectional dynamics of gender, race, and class; and argues that these dynamics influence, if not dictate, the quality of their in-school and life experiences. I then identify new directions for research and practice that recognize and build upon inner-city students' intersectional identities, urging policy initiatives that promote educational success while advancing equal educational opportunity.